How PCs Replicate Inequality. (Wilson Quarterly)
Presents a review of the article `Home Computers and School Performance,' by Paul Attewell and Juan Battle from the January-March 1999 issue of `The Information Society,' which deals with the influence of computers on the academic performance of children.